Analisis Dan Perancangan Sistem Lelang Online Pakaian Second Bermerek Berbasis Web Menggunakan Metode Extreme Programming - Arnold Agusti Pratama; Ines Heidiani Ikasari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
One of the business activities that are currently starting to develop is auction activities. Auction is the sale of goods with a price offer that is open to the public and is carried out orally and/or in writing which is decreasing or increasing to reach the highest price. The buyer with the highest bid wins the auction and completes the payment transaction. Branded second-hand clothes are one of the fashion trends, especially among teenagers, because most people consider second-hand clothes to be a unique and classic fashion so that they become one of the public's targets for getting a different style. The auction system for second hand branded clothes is still mostly traditional, in which the buyer must come to the auction shop to see the branded second hand clothes firsthand. In addition, auctions are only held during opening hours. Of course, buyers should spend more time following the auction through to the end. This is less effective and efficient because of distance and time constraints. To provide a solution to this problem, an online auction system for branded second-hand clothes was created that serves as a means for many buyers to facilitate auction activities. The development of this online auction system uses the Extreme Programming (XP) method and the database uses MySQL and the programming language uses PHP. The results of this study are an online auction system for web-based second-hand clothes that can simplify the auction process and can hold auctions and be accessed for 24 hours. In addition, this system can make it easier to make bids, search for auction winners, and transactions.